A Few Misconceptions about Cultural Evolution - O’Brien Michael J. (Cultural Science)
Despite a growing number of social scientists who view the evolution of culture as a Darwinian process, research in the field at large is still rooted in the orthogenetic, progressive models of cultural evolution that were popularized in the nineteenth century and brought back in a new form in the mid-twentieth century. This is unfortunate because it shifts the focus away from the fact that cultural evolution is driven by some exceedingly complicated and highly interesting mechanisms that await further analytical attention. A better understanding of human behaviour, which is at the heart of cultural evolution, depends on a general recognition that genes and culture are not separately evolving entities but rather co-evolving components of the human enterprise.